DSS Sistem Pendukung Keputusan Penilaian Kinerja Guru Terbaik pada TK IT AN-NUR Menggunakan Metode Graphic Rating Scales - Dhiva Andini Putri Alinur; Sri Lestari; Dadang Iskandar Mulyana; Wahyu Saputro (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2021)
The development of technological sophistication today, is needed in various fields, especially in the field of education. Technology is needed in the field of education to make it easier for schools to obtain data, provide teaching and assess the development of schools, teachers, and students to be more efficient, fast and effective. Schools are where students receive guidance and instruction from educators or teachers. The quality of an educator is needed in realizing smart, skilled, and creative students. Therefore, they are required to have their own advantages that will make them the best teachers. Teacher performance is needed to improve the quality and quality of an educator. With a good community assessment of the TK IT An-Nur, teachers have a responsibility to always improve the quality and quality. Kindergarten teachers are required to be creative in guiding students, not only introduce children to lessons but also introduce children about manners and moral daily life. TK IT An-nur still uses a manual and has not been computerized in the assessment of teacher performance, so in determining the best teacher in each year is still groping. With the best teacher decision support system with graphic rating scales method, it can facilitate principals and operators in the performance assessment process and get accurate results.